Prediksi puncak wabah Covid-19 di Indonesia menggunakan model logistik dan forecasting dengan FB Prophet - Fakhoor Izaaz Wildhanrahman; Chamdan Laylan Abdulbaaqiy; Muhammad Farhan Dirhami (Unri Conference Series: Community Engagement, 2020)
Covid-19 has infected many people in Indonesia, with the number of confirmed cases increasing every day; around 315,714 people have been confirmed positive for Covid-19 (data on 7 October 2020 from the covid19.go.id website). The author's team conducted this analysis intending to create a time series model of the total number of people infected with Covid-19 and predict the peak of the Covid-19 outbreak in Indonesia with the hope that the resulting model can be an initial guideline in preparation for the peak of the Covid-19 outbreak in Indonesia. The author's team analyzed logistic models and forecasting models with FB Prophet. Prediction using the logistic model results in the maximum number of cases (during peak conditions) in Indonesia of 669,595, with the peak of the outbreak occurring after 870 days (calculated starting on October 7, 2020), namely on June 22, 2022. This is proven and can be compared with the results of forecasting analysis with FBProphet. In a forecasting analysis using FB Prophet, the results show that cases of Covid-19 infection in Indonesia will continue to rise. This analysis results in a prediction that on October 22, 2020, there will be 375,393 people infected with Covid-19 in Indonesia.